Accelerating wastewater-based SARS-CoV-2 surveillance using a mobile laboratory in mixed infrastructure regions - Amirmohammad Sakhaei; Soroosh Torabi; Mohammad Dehghan Banadaki; Alexus Rockward; William D. Strike; Soroush Farahbakhsh; David Graf; August Bodin; Amanda Muzzey; Riley Lang; Sara Ignoffo; Sean Haley; et al. (Science of The Total Environment, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Physician Assessment of Non-Medical Toxin Switching on Patient Care - David Charles; Lily Venditti; Mariana Nelson; Ritu Singh; Kian Pazira; Haley Kling; Leeza Kopaeva; Sheffield Sharp; Kelly Harper (Toxicon, 2026)

Patient Perspectives on Nonmedical Toxin Switching and Care - David Charles; Lily Venditti; Mariana Nelson; Ritu Singh; Kian Pazira; Haley Kling; Leeza Kopaeva; Sheffield Sharp; Kelly Harper (Toxicon, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Encapsulation of the lipidated TLR7/8 agonist INI-4001 into ionic liposomes impacts H7 influenza antigen-specific immune responses - Fatemeh Mehradnia; Hardik Amin; Maria E. Ferrini; Haley Partlow; Timothy Borgogna; Soma Shekar Dachavaram; Kendal T. Ryter; Hélène G. Bazin; Jay T. Evans; David J. Burkhart; Blair DeBuysscher; Walid M. Abdelwahab (Drug Delivery and Translational Research, 2026)
Toll-like receptors (TLRs) are the best characterized family of Pattern Recognition Receptor-targeting adjuvants. Activation of TLR7/8 in particular, enhances antigen presentation by dendritic cells and macrophages, boosting Th1-mediated adaptive immune responses. However, poor pharmacokinetics and systemic toxicity of some TLR7/8 ligands hinder their clinical translation. Lipidation and incorporation of TLR7/8 ligands into liposomes can reduce systemic exposure, improve pharmacokinetics, pharmacodynamics, and presentation to immune cells. In the present study, a series of liposomal formulations incorporating a novel lipidated TLR7/8 agonist, INI-4001, were prepared to evaluate the effect of surface charge and lipid composition on the colloidal stability, cytotoxicity, innate immune activation, and adjuvant activity when combined with the recombinant Influenza A/Shanghai/1/13 (H7N9) Virus Hemagglutinin antigen (H7). The tested formulations include neutral (DOPC/Cholesterol), anionic (DOPG/Cholesterol), and cationic (DOPC/DC-Cholesterol, DOPC/GL67, DOEPC/Cholesterol, DOTAP/Cholesterol, or DOTAP + DDAB/Cholesterol) liposomes. These studies demonstrated that alongside the type and magnitude of particle surface charge, lipid composition was a determining factor in the regulation of immunogenicity and biocompatibility of INI-4001-loaded liposomes. Among the cationic liposomes evaluated, DOPC/DC-Cholesterol liposomes exhibited the lowest in vitro cytotoxicity while enhancing TNF-α induction from human peripheral blood mononuclear cells. Furthermore, murine immunization studies demonstrated that the same formulation enhanced H7-specific IgG titers and induced a Th1-polarized cell-mediated response compared to H7 antigen alone or the matched liposome lacking INI-4001. Of note, the anionic DOPG/Cholesterol INI-4001 liposomes induced a rapid response with significantly higher IgG titers after a single immunization and promoted strong Th1-polarized cellular responses, which may be advantageous in an influenza pandemic setting. These findings highlight the key role of liposome characteristics in optimizing the safety and immunogenicity of TLR7/8 agonist-adjuvanted subunit influenza vaccines.

A novel model quantifies epiphyte-mediated temperature and water dynamics in a tropical montane cloud forest - David Carchipulla-Morales; Haley Corbett; Damon Vaughan; Sybil G. Gotsch; Todd E. Dawson; Nalini Nadkarni; Lauren E.L. Lowman (Agricultural and Forest Meteorology, 2025)

Within-farm spatiotemporal variability impacts carrot yield and quality more than preceding cover crop on a Canadian organic farm - Haley A. Catton; Francis J. Larney; Thomas A. Forge; David M. Shack; Henry Wai Chau; Charles M. Geddes; Newton Z. Lupwayi; Bobbi L. Helgason (Organic Agriculture, 2025)
Carrot ( Daucus carota ) is an important crop grown in Canada and globally. Fresh market carrots have strict cosmetic requirements to command full value at “Grade A” and are frequently downgraded for irregular shape, size, or pest damage. Organic farming presents challenges for nutrient management, soil health and pest control, which may be mitigated with cover cropping. A 3-year field experiment was conducted on a commercial organic farm to 1) test the effects of six preceding-year cover crop treatments compared to a weedy fallow control on carrot yield and quality, wireworm damage, reasons for downgrading, and populations of plant parasitic nematodes, and 2) characterize within-farm spatiotemperal variability in production to identify strategies to improve and stabilize economic return. Carrot yield (42–55 Mg ha −1 ), quality (39–92% Grade A) and market value (183–221 $1000 Canadian dollars ha −1 ) varied drastically across years, and blocks within years (≤ 20% differences), but cover crops had no impact on these metrics. The dominant reasons for downgrading were morphological, affecting 7–74% of carrots each year and varying with cover crop only once, where carrots following buckwheat ( Fagopyrum esculentum ) had fewer shape flaws. Nematodes had no relationship to cover crop or any carrot metric and wireworms damaged only 2% of carrots across all three years. This study found virtually no effect of cover crop species composition on next year’s carrots on this farm, and that the farmer-collaborators can optimize their operation by improving crop establishment across space and time, reducing morphological flaws, and seeking higher value for downgraded produce.

A Comparison of Dietary Intake Among Rural Americans With and Without Diabetes - Christian A. Koziatek; Melissa Rony; Carolina Quintero Arias; Tammy Flores; Matthew Heider; Molly Smith; Sadakat Chowdhury; Haley Motola; Jill Hubert-Simon; Karen Holden; David C. Lee (Journal of Nutrition Education and Behavior, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Effectiveness of ozone nanobubble treatments on high biomass cyanobacterial blooms: A mesocosm experiment and field trial - Justin D. Chaffin; David E. Berthold; Eugene C. Braig; Josh D. Fuchs; Rachel S. Gabor; Stephen J. Jacquemin; Haley E. Kuhn; Lillian D. Labus; H. Dail Laughinghouse; Forrest W. Lefler; Heath E. Mash; Heather A. Raymond; et al. (Journal of Environmental Management, 2024)

Confined within a sugarcane monoculture: A participatory assessment of water pollution and potential health risks in the community of El Tiple, Colombia - David Bahamón-Pinzón; Irene Vélez-Torres; Shanna L. Estes; Cindy Lee; Arelis Moore; William Bridges; Elizabeth Carraway; Haley Blazer; Héctor Mario Gutiérrez Zapata; Diana Vanegas (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

The detection of a strong episignature for Chung–Jansen syndrome, partially overlapping with Börjeson–Forssman–Lehmann and White–Kernohan syndromes - Niels Vos; Sadegheh Haghshenas; Liselot van der Laan; Perle K. M. Russel; Kathleen Rooney; Michael A. Levy; Raissa Relator; Jennifer Kerkhof; Haley McConkey; Saskia M. Maas; Lisenka E. L. M. Vissers; Bert B. A. de Vries; et al. (Human Genetics, 2024)
Chung-Jansen syndrome is a neurodevelopmental disorder characterized by intellectual disability, behavioral problems, obesity and dysmorphic features. It is caused by pathogenic variants in the PHIP gene that encodes for the Pleckstrin homology domain-interacting protein, which is part of an epigenetic modifier protein complex. Therefore, we hypothesized that PHIP haploinsufficiency may impact genome-wide DNA methylation (DNAm). We assessed the DNAm profiles of affected individuals with pathogenic and likely pathogenic PHIP variants with Infinium Methylation EPIC arrays and report a specific and sensitive DNAm episignature biomarker for Chung–Jansen syndrome. In addition, we observed similarities between the methylation profile of Chung–Jansen syndrome and that of functionally related and clinically partially overlapping genetic disorders, White–Kernohan syndrome (caused by variants in DDB1 gene) and Börjeson–Forssman–Lehmann syndrome (caused by variants in PHF6 gene). Based on these observations we also proceeded to develop a common episignature biomarker for these disorders. These newly defined episignatures can be used as part of a multiclass episignature classifier for screening of affected individuals with rare disorders and interpretation of genetic variants of unknown clinical significance, and provide further insights into the common molecular pathophysiology of the clinically-related Chung–Jansen, Börjeson–Forssman–Lehmann and White–Kernohan syndromes.

Satellite tracking reveals use of Biscayne National Park by sea turtles tagged in multiple locations - Kristen M. Hart; Allison M. Benscoter; Haley M. Turner; Michael S. Cherkiss; Andrew G. Crowder; Jacquelyn C. Guzy; David C. Roche; Chris R. Sasso; Glenn D. Goodwin; Derek A. Burkholder (Regional Studies in Marine Science, 2023)

Northerly range expansion and first confirmed records of the smalltooth sand tiger shark, Odontaspis ferox , in the United Kingdom and Ireland - David J. Curnick; Rob Deaville; Jenny R. Bortoluzzi; Luke Cameron; Jeanette E. L. Carlsson; Jens Carlsson; Haley R. Dolton; Cat A. Gordon; Phil Hosegood; Alicia Nilsson; Matthew W. Perkins; Kevin J. Purves; et al. (Journal of Fish Biology, 2023)
Three Odontaspis ferox (confirmed by mtDNA barcoding) were found in the English Channel and Celtic Sea in 2023 at Lepe, UK (50.7846, −1.3508), Kilmore Quay, Ireland (52.1714, −6.5937), and Lyme Bay, UK (50.6448, −2.9302). These are the first records of O. ferox in either country, and extend the species' range by over three degrees of latitude, to >52° N. They were ~275 (female), 433 (female), and 293 cm (male) total length, respectively. These continue a series of new records, possibly indicative of a climate change−induced shift in the species' range.

Lower muscle mitochondrial energetics is associated with greater phenotypic frailty in older women and men: the Study of Muscle, Mobility and Aging - Theresa Mau; Haley N. Barnes; Terri L. Blackwell; Philip A. Kramer; Scott R. Bauer; David J. Marcinek; Sofhia V. Ramos; Daniel E. Forman; Frederico G. S. Toledo; Russell T. Hepple; Stephen B. Kritchevsky; Steven R. Cummings; et al. (GeroScience, 2023)

Household hurricane evacuation during a dual-threat event: Hurricane Laura and COVID-19 - Alex Greer; David Huntsman; Hao-Che Wu; Haley Murphy; Lauren Clay (Transportation Research Part D: Transport and Environment, 2023)

A Qualitative Study of Factors Influencing Food Choices and Food Sources Among Adults Aged 50 Years and Older During the Coronavirus Disease 2019 Pandemic - Patrick J. Brady; Natoshia M. Askelson; Helaina Thompson; Sarah Kersten; Haley Hopkins; Sato Ashida; Faryle Nothwehr; Brandi Janssen; David Frisvold (Journal of the Academy of Nutrition and Dietetics, 2023)

Microbial community transcriptional patterns vary in response to mesoscale forcing in the North Pacific Subtropical Gyre - Matthew J. Harke; Kyle R. Frischkorn; Gwenn M. M. Hennon; Sheean T. Haley; Benedetto Barone; David M. Karl; Sonya T. Dyhrman (Environmental Microbiology, 2021)
Summary The physical and biological dynamics that influence phytoplankton communities in the oligotrophic ocean are complex, changing across broad temporal and spatial scales. Eukaryotic phytoplankton (e.g., diatoms), despite their relatively low abundance in oligotrophic waters, are responsible for a large component of the organic matter flux to the ocean interior. Mesoscale eddies can impact both microbial community structure and function, enhancing primary production and carbon export, but the mechanisms that underpin these dynamics are still poorly understood. Here, mesoscale eddy influences on the taxonomic diversity and expressed functional profiles of surface communities of microeukaryotes and particle‐associated heterotrophic bacteria from the North Pacific Subtropical Gyre were assessed over 2 years (spring 2016 and summer 2017). The taxonomic diversity of the microeukaryotes significantly differed by eddy polarity (cyclonic versus anticyclonic) and between sampling seasons/years and was significantly correlated with the taxonomic diversity of particle‐associated heterotrophic bacteria. The expressed functional profile of these taxonomically distinct microeukaryotes varied consistently as a function of eddy polarity, with cyclones having a different expression pattern than anticyclones, and between sampling seasons/years. These data suggest that mesoscale forcing, and associated changes in biogeochemistry, could drive specific physiological responses in the resident microeukaryote community, independent of species composition.

The COVID-19 pandemic: local to global implications as perceived by urban ecologists - Ian Douglas; Mark Champion; Joy Clancy; David Haley; Marcelo Lopes de Souza; Kerry Morrison; Alan Scott; Richard Scott; Miriam Stark; Joanne Tippett; Piotr Tryjanowski; Tim Webb (Socio-Ecological Practice Research, 2020)
The global COVID-19 pandemic is affecting everyone, but in many different ways, stimulating contrasting reactions and responses: opportunities for some, difficulties for many. A simple survey of how individual workers in urban ecology have been coping with COVID-19 constraints found divergent responses to COVID-19 on people’s activities, both within countries and between continents. Many academics felt frustrated at being unable to do fieldwork, but several saw opportunities to change ways of working and review their engagement with the natural world. Some engaging with social groups found new ways of sharing ideas and developing aspirations without face-to-face contact. Practitioners creating and managing urban greenspaces had to devise ways to work and travel while maintaining social distancing. Many feared severe funding impacts from changed local government priorities. Around the world, the COVID-19 pandemic has amplified issues, such as environmental injustice, disaster preparation and food security, that have been endemic in most countries across the global south in modern times. However, developing and sustaining the strong community spirit shown in many places will speed economic recovery and make cities more resilient against future geophysical and people-made disasters. Significantly, top-down responses and one-size-fits-all solutions, however good the modelling on which they are based, are unlikely to succeed without the insights that local knowledge and community understanding can bring. We all will have to look at disaster preparation in a more comprehensive, caring and consistent way in future.

Taxonomic and geographic gaps in understanding the functional effects of imperilled fishes on freshwater ecosystems - Eric K. Moody; Ellen Albright; Katie Cope; Rachel Fleck; Haley Grigel; David Ortiz; Grace M. Wilkinson (Fish and Fisheries, 2019)
The effects that fishes have on rates of one or more ecosystem processes (hereafter referred to as functional effects) are often invoked as an important reason for imperilled species conservation. However, the degree to which we understand these effects is rarely evaluated for most groups of fishes. We assessed how well the functional effects of freshwater and diadromous fishes, one of the most imperilled groups of animals, are quantified to date. We found that 88% of studies considering the functional effects of imperilled North American fishes were conducted on one family, Salmonidae. Studies of the functional effects of fishes were also concentrated in Pacific drainages of North America, with few studies in hotspots of imperilled fish diversity such as the Southeastern United States, the arid Southwest and central Mexico. Our results demonstrate the vast taxonomic and geographic gaps in our functional understanding of imperilled fishes and highlight the need to broaden this work to justify the argument that they are functionally important in the ecosystems they inhabit.

A comparison of genomic islands of differentiation across three young avian species pairs - Darren E. Irwin; Borja Milá; David P. L. Toews; Alan Brelsford; Haley L. Kenyon; Alison N. Porter; Christine Grossen; Kira E. Delmore; Miguel Alcaide; Jessica H. Irwin (Molecular Ecology, 2018)
Detailed evaluations of genomic variation between sister species often reveal distinct chromosomal regions of high relative differentiation (i.e., “islands of differentiation” in F ST ), but there is much debate regarding the causes of this pattern. We briefly review the prominent models of genomic islands of differentiation and compare patterns of genomic differentiation in three closely related pairs of New World warblers with the goal of evaluating support for the four models. Each pair (MacGillivray's/mourning warblers; Townsend's/black‐throated green warblers; and Audubon's/myrtle warblers) consists of forms that were likely separated in western and eastern North American refugia during cycles of Pleistocene glaciations and have now come into contact in western Canada, where each forms a narrow hybrid zone. We show strong differences between pairs in their patterns of genomic heterogeneity in F ST , suggesting differing selective forces and/or differing genomic responses to similar selective forces among the three pairs. Across most of the genome, levels of within‐group nucleotide diversity ( π Within ) are almost as large as levels of between‐group nucleotide distance ( π Between ) within each pair, suggesting recent common ancestry and/or gene flow. In two pairs, a pattern of the F ST peaks having low π Between suggests that selective sweeps spread between geographically differentiated groups, followed by local differentiation. This “sweep‐before‐differentiation” model is consistent with signatures of gene flow within the yellow‐rumped warbler species complex. These findings add to our growing understanding of speciation as a complex process that can involve phases of adaptive introgression among partially differentiated populations.

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Tolerance of wheat to vegetative stage soil waterlogging is conditioned by both constitutive and adaptive QTL - Diana C. Ballesteros; R. Esten Mason; Christopher K. Addison; M. Andrea Acuña; M. Nelly Arguello; Nithya Subramanian; Randall Galen Miller; Haley Sater; Edward E. Gbur; David Miller; Carl A. Griffey; Marla D. Barnett; et al. (Euphytica, 2015)

New science challenges old notion that mercury dental amalgam is safe - Kristin G. Homme; Janet K. Kern; Boyd E. Haley; David A. Geier; Paul G. King; Lisa K. Sykes; Mark R. Geier (BioMetals, 2014)

Abdominal Tubercles of Adult Male Camel Crickets, Pristoceuthophilus marmoratus Rehn (Orthoptera: Rhaphidophoridae), Produce Cues Attractive to Females - Estenia Lisseth Haley; David A. Gray (Journal of Insect Behavior, 2013)

Variation in foliar nitrogen and albedo in response to nitrogen fertilization and elevated CO2 - Haley F. Wicklein; Scott V. Ollinger; Mary E. Martin; David Y. Hollinger; Lucie C. Lepine; Michelle C. Day; Megan K. Bartlett; Andrew D. Richardson; Richard J. Norby (Oecologia, 2012)

Inducible expression of TGFβ, Snail and Zeb1 recapitulates EMT in vitro and in vivo in a NSCLC model - Gretchen M. Argast; Joseph S. Krueger; Stuart Thomson; Isabela Sujka-Kwok; Krista Carey; Stacia Silva; Matthew O’Connor; Peter Mercado; Iain J. Mulford; G. David Young; Regina Sennello; Robert Wild; et al. (Clinical & Experimental Metastasis, 2011)

A systems view of epithelial–mesenchymal transition signaling states - Stuart Thomson; Filippo Petti; Izabela Sujka-Kwok; Peter Mercado; James Bean; Melissa Monaghan; Sean L. Seymour; Gretchen M. Argast; David M. Epstein; John D. Haley (Clinical & Experimental Metastasis, 2011)

Kinase switching in mesenchymal-like non-small cell lung cancer lines contributes to EGFR inhibitor resistance through pathway redundancy - Stuart Thomson; Filippo Petti; Izabela Sujka-Kwok; David Epstein; John D. Haley (Clinical & Experimental Metastasis, 2008)

Bypassing cellular EGF receptor dependence through epithelial-to-mesenchymal-like transitions - Sharon Barr; Stuart Thomson; Elizabeth Buck; Suzanne Russo; Filippo Petti; Izabela Sujka-Kwok; Alexandra Eyzaguirre; Maryland Rosenfeld-Franklin; Neil W. Gibson; Mark Miglarese; David Epstein; Kenneth K. Iwata; et al. (Clinical & Experimental Metastasis, 2008)

Linkage mapping of the locus for inherited ovine arthrogryposis (IOA) to sheep Chromosome 5 - Angela M. Murphy; David E. MacHugh; Stephen D.E. Park; Erik Scraggs; Chris S. Haley; David J. Lynn; Maurice P. Boland; Michael L. Doherty (Mammalian Genome, 2007)

Is alpha-Pinene a Substrate for Permeability-Glycoprotein in Wood Rats? - Adam K. Green; Shannon L. Haley; David M. Barnes; M. Denise Dearing; William H. Karasov (Journal of Chemical Ecology, 2006)

Effects of nitrate on the interactions of the tadpoles of two ranids (Rana clamitans and R. catesbeiana) - Geoffrey R. Smith; Kathleen G. Temple; Haley A. Dingfelder; David A. Vaala (Aquatic Ecology, 2006)

Modeling Sustainability of Arctic Communities: An Interdisciplinary Collaboration of Researchers and Local Knowledge Holders - Jack A. Kruse; Robert G. White; Howard E. Epstein; Billy Archie; Matt Berman; Stephen R. Braund; F. Stuart Chapin; Johnny Charlie; Colin J. Daniel; Joan Eamer; Nick Flanders; Brad Griffith; et al. (Ecosystems, 2004)

Distribution and abundance of macroinvertebrates within two temporary ponds - Geoffrey R. Smith; David A. Vaala; Haley A. Dingfelder (Hydrobiologia, 2003)

Will Consumers Pay More for Certified Wood Products? - Keith Forsyth; David Haley; Robert Kozak (Journal of Forestry, 1999)
Insight into customers' attitudes toward certified wood products can help gauge whether a viable market exists. When buying wood products, people in our sample--300 customers in the British Columbia home improvement market--shop first for quality and then for price. Although environmental attributes, including certification, are less important than many other criteria that consumers consider, some say that they are willing to pay a premium for certified wood products; whether they would actually do so is another question. Cluster analysis provides a profile of the consumers who might be likely to purchase certified wood products.